Mediterranean diet enriched in extra-virgin olive oil or nuts modulates circulating exosomal non-coding RNAs. - Mantilla-Escalante, Diana C.; López de las Hazas, María-Carmen; Crespo, M. Carmen; Martín-Hernández, Roberto; Tomé-Carneiro, Joao; del Pozo-Acebo, Lorena; Salas-Salvadó, Jordi; Bulló, Mónica; Dávalos, Alberto (European Journal of Nutrition, 2021)
Purpose: Exosomes are extracellular vesicles secreted by cells, which can transport different molecules, including nucleic acids. Dietary habits may induce gene regulation through the modulation of exosomal RNAs. We aimed at characterizing exosomal lncRNAs, mRNA and miRNAs modulation after a 1-year adherence to a low-fat diet (LFD) or to Mediterranean-based diets enriched in extra-virgin olive oil (MedDiet + EVOO) or in a mixture of nuts (MedDiet + Nuts). Methods: Plasma samples were collected, at baseline and after 1 year of dietary interventions, from 150 participants included in the PREDIMED study (Reus Center). LncRNAs, mRNAs and miRNAs were isolated from plasma exosomes and screened. RT-qPCR validation was performed for miRNAs. Results: Compared with LFD, 413 lncRNAs and 188 mRNAs, and 476 lncRNAs and 235 mRNAs were differentially modulated in response to the MedDiet + EVOO and MedDiet + Nuts interventions, respectively. In addition, after 1 year of dietary interventions, 26 circulating miRNAs were identified as differentially expressed between groups. After 1 year of intervention, 11 miRNAs significantly changed in LFD group, while 8 and 21 were modulated in response to the MedDiet enriched with EVOO or nuts, respectively. Bioinformatic analyses of differentially expressed miRNAs and their validated target genes suggest certain metabolic pathways are modulated by LFD (PI3K-Akt and AMPK), MedDiet + EVOO (PI3K-Akt, NF-kappa B, HIF-1, and insulin resistance), and MedDiet-Nuts (FoxO, PI3K-Akt, AMPK, p53 and HIF-1) interventions. Conclusion: Results show that 1-year MedDiet + Nuts and MedDiet + EVOO dietary interventions modulate exosomal RNA content, with the former affecting a higher number of miRNAs. The modulation of exosomal RNAs could help explain how the adherence to a Mediterranean diet may lead to beneficial effects and deserves further investigation.